Komunikasi Orang Tua Tentang Seksualitas Terhadap Perilaku Seksual Pranikah Pada Remaja - Isna Wanufika; Sumarni Sumarni; Djauhar Ismail (Berita Kedokteran Masyarakat (BKM), 2017)
Parents' communication about sexuality to premarital sexual behavior in adolescentsPurposeThis research aimed to examine the relationship between parent-child communication about sexuality and adolescents premarital sexual behavior.MethodsThis research involved 205 students in Senior High School "A" Yogyakarta. Data analysis was conducted with chi-square and logistic regression tests.ResultsThis research showed that there was no significant correlation (p > 0.05) between parental communication about sexuality and premarital sexual behavior in adolescents with OR score 1.43 (95% CI; 0.78- 2.63). The results of parental communication analysis of sexuality after considering other variables: such as gender, self-efficacy, and alcohol/drug used accounted for 5.7% in at-risk premarital sexual behavior.ConclusionThere were no significant correlations between parent-child communication about sexuality and adolescents’ premarital sexual behavior.